2011
DOI: 10.1177/1059840511426577
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sexual Risk Communication With Adolescents Using Event History Calendars

Abstract: This study was conducted to explore the effects of an event history calendar (EHC) approach on adolescent sexual risk communication and sexual activity. Adolescent school-linked health clinic patients (n = 30) who reported sexual activity self-administered the EHC that was used by nurse practitioners (NPs; n = 2) during a clinic visit. Immediately pre- and post-visit, and at 1 and 3 months, adolescents reported sexual risk behaviors and perceptions about EHC communication on questionnaires and by interview. NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 18 publications
1
35
0
1
Order By: Relevance
“…However, these preliminary findings are encouraging and build on previous research by Martyn and colleagues (Martyn & Martin, 2003;Martyn et al, 2006;Martyn et al, 2011) to provide direction for further testing of this instrument. Future studies should explore ways the SHHC could be modified to be more easily administered with specific subgroups of young people who may be unable to complete it independently (e.g., patients at different reading levels, those with emotional or other disabilities).…”
Section: Discussionsupporting
confidence: 60%
“…However, these preliminary findings are encouraging and build on previous research by Martyn and colleagues (Martyn & Martin, 2003;Martyn et al, 2006;Martyn et al, 2011) to provide direction for further testing of this instrument. Future studies should explore ways the SHHC could be modified to be more easily administered with specific subgroups of young people who may be unable to complete it independently (e.g., patients at different reading levels, those with emotional or other disabilities).…”
Section: Discussionsupporting
confidence: 60%
“…Past work using the EHCs with adolescents have demonstrated improved communication scores with five scales constructed by Martyn and colleagues (2012a) to evaluate amount of communication, satisfaction with communication, mutuality of communication, client involvement in decision-making, and client satisfaction with interpersonal style. The independent variables included in this study were the youth participant’s intervention group (EHC versus GAPS) and descriptive demographic measures (e.g., age, race, ethnicity, gender, education, employment, living situation, health insurance, and past healthcare interactions).…”
Section: Methodsmentioning
confidence: 99%
“…This study utilized modified versions of the communication scales originally used by Martyn and colleagues (2012a) in which problematic questions or those that elicited a lower reliability in the previous study were changed or removed. All questions are scored on a Likert response scale from 1 to 5 with a score of 5 indicating maximum quantity (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first known studies to apply a life or event history calendar to assess adolescent sexual risk, Martyn and colleagues found that adolescents' recall of risk-taking behaviors over the previous 6 to 10 years and perceptions of communication with providers could be enhanced using an event history calendar without increasing the scheduling or resource burden for staff. Results indicated that youth reporting sexual activities on the calendar were prone to reflect on their levels of risk and express the intention to change their risky behaviors (Martyn, Reifsnider, & Murray, 2006;Martyn et al, 2011). In general, participants using the EHC reported satisfaction with the instrument as well as ease of use, with time of completion ranging from 5 minutes to 1 hour; and nurse interviewers described the ease with which it allowed them to discuss patterns of risk as well as triggers for sexual behaviors with patients (Martyn & Martin, 2003).…”
Section: School Of Social Work University Of Minnesotamentioning
confidence: 94%